Current Diagnosis and Treatment of Kala-azar: Bangladesh Perspective - Ahasan, HAM Nazmul; Ayaz, KFM; Bari, Md Shafiqul (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3329/jom.v9i1.1426 J MEDICINE 2008; 9 : 45-49